Lactic acid bacteria with antimicrobial properties isolated from the instestines Of Japanese Quail (Coturnix coturnix Japonica) - Zaidi, Nurul Amani; Abdul Hamid, Azzmer Azzar; Tengku Abdul Hamid, Tengku Haziyamin (Razi Publishing, 2017)
Lactic acid bacteria (LAB) confer many advantages to humans and animals and they provide natural protection against bacterial pathogens such as Salmonella typhymurium and Eschericia coli. LAB strains have been isolated from various animal sources but from this research LAB were isolated from quail’s (Coturnix coturnix Japonica) intestine. About 12 strains were isolated from the quail’s intestine; and out of these, 5 samples (S1-1B, S2-1A, S2- 1B, S2-2B and S3-1A) produced lactose on lactose test. All of these strains appeared to be non-motile coccus with gram positive morphology, catalase-negative and oxidase-negative. These strains showed antimicrobial activities (inhibition zones) against indicator bacterium, i.e., Staphylococcus aureus, Escherichia coli and Salmonella typhimurium using agar well methods. PCR amplification of 16S ribosomal RNA revealed that these five isolates show highest sequence similarity with other LAB strains isolated from other animals which include common genera such as Enterococcus and Lactobacillus. Strain S1-1B, S2-1B and S2-2B were highly similar with Enterococcus faecium, strain S3-2B with Enterococcus durans and S2-1A with Lactobacillus salivarius. This work shows that common LAB species were isolated from intestinal tissues of Malaysian quail (Coturnix Japonica) which were able to produce antimicrobial activities against pathogenic strains.